Congenital absence of the portal vein in a cat - Andrew Holloway; Louise Groot; Klaartje van der Schaaf (Journal of Feline Medicine and Surgery Open Reports, 2018)
Case summary A 9-month-old female neutered domestic shorthair cat presented with a history of episodic ptyalism, lethargy and abnormal behaviour. The clinical signs together with elevated pre- and post-prandial bile acid concentrations were consistent with hepatic encephalopathy (HE). In the absence of a portosystemic shunt (PSS) on abdominal ultrasound, medical management of HE was established with a protein-restricted diet and lactulose and the neurological signs resolved. Following an episode of acute vomiting and haemorrhagic diarrhoea at 19 months of age abdominal ultrasonography was repeated. The portal vein could not be demonstrated ultrasonographically; instead, portal vein tributaries were tortuous and communicated with the caudal vena cava (CdVC) at the level of the left kidney. CT angiography (CTA) confirmed the absence of the portal vein. CTA demonstrated the tortuous terminations of the portal tributaries, and several systemic veins, draining into the CdVC via a large-diameter paracaval vessel at the level of the left kidney. Gastrointestinal signs were stabilised and medical management for HE of a protein-restricted diet and lactulose was re-established. Relevance and novel information Congenital absence of the portal vein has not been described previously in the cat and should be considered in cats presenting with signs suggestive of a PSS and HE. The portal vein in the cat can be demonstrated using ultrasound, but complex congenital vascular malformations of the portal or systemic abdominal veins should be characterised using CTA and further distinguished from other vascular anomalies that may present with similar ultrasonographic features.